MODEL PENDEKATAN ALAT UJI KEPADATAN RINGAN UNTUK TANAH DI LABORATORIUM - Anwar Muda (INFO-TEKNIK, 2016)
The study is motivated, that during compaction test light to ground in the laboratory with standard equipment ISO 1742: 2008. However, this equipment has not been done as a benchmark or model approaches that have the same standards with ISO 1742: 2008 with a margin of error of ≤ 5%. This study aims to determine whether the test equipment density of light to the ground in a laboratory with a model can be used as a means of testing the density of light to the ground in a laboratory with the same standards as ISO 1742: 2008 with a margin of error of ≤ 5% and give the same assessment of the performance heap.The research method with a step that is preparing the soil samples are clay Palangkaraya and 2 pieces of light density test equipment is ISO 1742: 2008 and the model. Then, the next step is to test the density of the two pieces of the tool.The results showed the maximum dry weight of 1,51 g / cm3 and the optimum water content and soil 25,74% including silt-loam with poor performance forecasts pile up good or clay with a pile of bad performance forecast to moderate. While the maximum density of clay based Model for 5, 10, and 15 collisions per layer and for 20 and 25 collisions per layer as much as 2 layers, obtained by bulk density maximum dry and optimum moisture content with a margin of error of <5% of the ISO 1742: 2008, but do not have the same ratings with ISO 1742: 2008 on the performance of the pile, so that the model has not been qualified as light density test equipment to the ground in a laboratory. For 30 collisions per layer as much as 2 layers, has a bulk density maximum dry and optimum moisture content with a margin of error of <5% of the ISO 1742: 2008 and similar assessments to ISO 1742: 2008 on the performance of the pile, then the model qualifies as test equipment light density to the ground in a laboratory and have the same standards SNI1742: 2008.